USE OF EDIBLE MUSHROOMS AND LICHENS IN ADDITIONAL NUTRITION OF PEOPLE IN WAR IN BOSNIA AND HERZEGOVINA (W. BALKAN) - Redzic, S.; Biscevic, A.; Redzic, A. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
All wars, historical and those in modern times, emphasize human nutrition as key issue [1]. Usually, conventional food is insufficient and people are trying to survive by using additional sources in wild plants, animals and mushrooms. Same situation was during the war in Bosnia and Herzegovina (1992-95). During several seasons in 2000-2006, researches were conducted on use of edible mushrooms and lichens in survival of people in isolated war areas in eastern Bosnia region, where war activities were extremely difficult and followed by killings of civilians, exoduses and total blockages. 35 adults were interviewed, all of different sex and age, who spent war period in occupied zones. By using method of ethno–botanical interview and direct field work, determined were 15 species of mushrooms and 5 species of lichens that were used in human nutrition. Most used mushrooms were as follows: Lactarius piperatus, Morchella conica, Agaricus campester, Boletus edulis, Boletus sp., Cantharellus cibarius, Russula sp., Tricholoma sp. and others. Most used lichens were following species: Evernia prunastri and Lobaria pulmonaria for making mash and lichen flour. Mushrooms were grilled or boiled, and some species were even used raw. Noted were also mushroom poisonings. Even though mushrooms are not most common nutrition ingredient in these areas, people, including soldiers, were forced to use mushrooms and lichens in order to survive. This is a good example of the fact that hunger and fear of hunger and very strong factor in human survival [2, 3]. References: 1.Redzic, S.J. (2006). Ecology of Food and Nutrition, 45, 189-232. 2. Redzic, S. (1999). Pharmacia, 10, 28-41. 3. Redzic, S. (2006b). Proceedings of the 1st IFOAM International Conference on Organic Wild Production, Teslic, BiH, 2006, 117-141.